Identification of novel amrR deletions as meropenem resistance mechanisms in clinical Burkholderia pseudomallei isolates - Supichaya Nimnuan-ngam; Shirley Yi Fen Hii; Rathanin Seng; Natnaree Saiprom; Sarunporn Tandhavanant; T. Eoin West; Narisara Chantratita (Microbiology Spectrum)
ABSTRACT Burkholderia pseudomallei, an environmental bacterium, is the causative agent of melioidosis, a potentially fatal infectious disease predominantly found in tropical regions. Despite the bacterium’s intrinsic resistance to numerous antibiotics, the antibiotic resistance mechanisms remain poorly understood. Recently, we identified novel partial deletions in the amrR gene of meropenem less-susceptible (MEM-LS) isolates (DR10212A, DR90049A, and DR90031E) obtained from patients with melioidosis. In this study, we performed mutagenesis and quantitative reverse-transcription real-time polymerase chain reaction (RT-qPCR) to validate the roles of these partial deletions in the amrR gene in MEM-LS isolates. By introducing wild-type amrR fragments from strain K96243 into three parental MEM-LS isolates, we successfully constructed three complemented mutant strains (DR10212A∷K96243-amrR, DR90049A∷K96243-amrR, and DR90031E∷K96243-amrR), which exhibited significantly decreased MEM minimum inhibitory concentrations (MIC) compared with their parental strains. Consistent with the decreased MIC, the expression levels of AmrAB-OprA efflux pump genes (oprA, amrB, and amrA) in the complemented mutant strains were downregulated at least 5-fold compared with the parental isolates, indicating the significant role of the partial amrR gene deletions in MEM-LS. Our findings provide more understanding of the MEM resistance mechanisms of clinical isolates of B. pseudomallei, thereby enhancing future strategies for the treatment and management of melioidosis.IMPORTANCEAntibiotic resistance of B. pseudomallei poses a significant threat to patients with melioidosis because it interferes with the recovery process and is associated with high mortality. This study reported that three new mutations involving efflux pumps in amrR (H92_S154del, V197del, and A202_R207del) confer resistance to MEM. These mutations were previously detected using whole genome sequencing (WGS) analysis of MEM-LS isolates from melioidosis patients in northeast Thailand. The data from this study provide more understanding of common mechanisms of drug resistance in B. pseudomallei. This information is essential for the development of more effective drugs for melioidosis treatment in the future.